Antimicrobial PLA-PVA multilayer films containing phenolic compounds. (1st May 2022) - Andrade, Johana; González-Martínez, Chelo; Chiralt, Amparo
Graphical abstract: Highlights: Active PLA/PVA/PLA three-layer films were successfully obtained by thermocompression. Carvacrol or ferulic acid as active compounds were incorporated into the PVA sheet. All multilayers exhibited tensile properties close to those of PLA monolayer films. Barrier capacity of the multilayers were greatly improved compared to the monolayers. Actives multilayers were effective at controlling the microbial growth of beef meat. Abstract: Multilayer materials with good interlayer-adhesion were obtained by thermocompression for laminating an internal poly (vinyl alcohol) (PVA) layer with two external poly (lactic acid) (PLA) layers. Carvacrol or ferulic acid were incorporated into the PVA sheet to obtain active materials. The multilayer films were characterised as to their microstructure, thermal behaviour, tensile and barrier properties. Furthermore, the antimicrobial capacity of the materials was analysed in packaged beef meat samples for 17 days at 5 °C. The laminates exhibited tensile properties close to those of the PLA films, but with enhanced stretchability. Compared to the monolayers, the barrier capacity of multilayers was much improved by combining polyester and PVA layers, which provide the laminate with water vapour and oxygen barrier capacity, respectively. Active multilayers were effective at controlling microbial growth in beef meat during cold storage. Therefore, the materials developed were functionally adequate for food packaging purposes and successfully promoted the meat preservation.